English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-01-30 08:05:02 · 4 answers · asked by rappernana13 1 in Science & Mathematics Mathematics

4 answers

3x + 13 = y = 2x +9 therefore, x = 9 - 13 = -4; y = -8 + 9 = 1

so, x = -4; y = 1;

2007-01-30 08:15:42 · answer #1 · answered by 1988_Escort 3 · 0 0

Add. Method.
y-3x=13 (1)
-y+2x=-9 (2)
________
0y-x=3 ; x=-3
remplace x=-3 in equation (1)
y-3(-3)=13
y+9=13
put (+9) in the other side;
y=13-9 ; y=3

S={-3,3}

2007-01-30 16:22:17 · answer #2 · answered by Johnny 2 · 0 0

2x = (3x + 13) - 9
2x = 3x + 4
x = -4
y = 3(-4) + 13
y = 1

2007-01-30 16:12:35 · answer #3 · answered by leaptad 6 · 1 0

2x = (3x + 13) - 9
2x = 3x + 4
x = -4
y = 3(-4) + 13
y = 1

2007-01-30 16:13:18 · answer #4 · answered by yakkyigooconroy 3 · 0 1

fedest.com, questions and answers